Evaluasi Sebaran Akar Kelapa Sawit (Elaeis guineensis Jacq.) dengan Tinggi Muka Air Tanah yang Berbeda - Ulama, Dio Alif; Bakri, Bakri (Seminar Nasional Lahan Suboptimal, 2022)
Ulama DA, Bakri B. 2022. Evaluation of distribution oil palm roots (Elaeis guineensis Jacq.) with different groundwater levels. In: Herlinda S et al. (Eds), Prosding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 682-694. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This research aimed to influence about groundwater levels and some soil physical properties on the distribution of palm oil roots. This research uses the observation method, then the data that has been obtained is presented in the form of tables and figures. To determine the effect of swamp distance and groundwater level depth on the distribution of oil palm roots, a T-test was carried out with a real level of 5%. In addition, Pearson (r) correlation and linear regression between the values of soil physical properties and the distribution of oil palm roots per soil depth were carried out. The results showed that the groundwater level did not have a significant effect on the value of oil palm root distribution. The physical properties of the soil in the form of color, moisture content, and total pore space have a positive correlation with the distribution value of the oil palm roots. But the value of bulk density has a negative correlation with the value of the distribution of oil palm roots. In this study, it was also found that texture has a positive influence on the distribution value of oil palm roots at 30 cm deep but has a negative influence on the distribution value of oil palm roots at depths of 60cm and 90 cm. So, the level of groundwater does not have a significant effect on the distribution of oil palm roots. However, the physical properties of soils have diverse correlations.